How Lives Come to Matter – Rethinking Mediation and Materiality in Autobiography (KULT_online, 2021)
Stories of the Self opens the purview of autobiography studies to come to terms with the proliferation of ‘self-life-inscription’ in media and matter beyond the book. In analyses of a variety of phenomena, Poletti argues that the material dimension of autobiographical practices fundamentally determines not only how they are produced and received but also what significance we attach to them. Innovatively combining theories from neighboring disciplines in this way, Poletti develops a number of specific ways of reading mediated lives and selves in their inescapable relationality.